Confronting Cognitive Anchoring Effect and Blind Spot Biases in Federal Sentencing: A Modest Solution for Reforming a Fundamental Flaw Criminal Laew - Bennett, Mark W. (Journal of Criminal Law and Criminology, 2014)
Disclaimer: This summary was generated by AI based on the content of the source document.